Lipidomic Analysis - Holčapek, Michal; Liebisch, Gerhard; Ekroos, Kim (Analytical chemistry, 2018)
The state-of-art in the lipidomic analysis is summarized here to provide the overview of available sample preparation strategies, mass spectrometry (MS)-based methods for the qualitative analysis of lipids, and the quantitative MS approaches for high-throughput clinical workflows. Major challenges in terms of widely accepted best practices for lipidomic analysis, nomenclature, and standards for data reporting are discussed as well.
Keywords: Lipids; Chromatography, High Pressure Liquid; Molecular Structure; lipidy; hmotnostní spektrometrie; vysokoúčinná kapalinová chromatografie; molekulární struktura; Mass Spectrometry